1998
DOI: 10.1302/0301-620x.80b1.7859
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire on the perceptions of patients about total knee replacement

Abstract: We have developed a 12-item questionnaire for patients having a total knee replacement (TKR). We made a prospective study of 117 patients before operation and at follow-up six months later, asking them to complete the new questionnaire and the form SF36. Some also filled in the Stanford Health Assessment Questionnaire (HAQ). An orthopaedic surgeon completed the American Knee Society (AKS) clinical score. The single score derived from the new questionnaire had high internal consistency, and its reproducibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
903
4
21

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,492 publications
(948 citation statements)
references
References 25 publications
20
903
4
21
Order By: Relevance
“…In addition, the impact of the extremely positive or negative outliers in function would have a greater impact with smaller cohorts, leading to increases in the SDs of the clinical outcome scores and perhaps masking true differences between the two groups. However, the SDs of the clinical outcomes scores seen in both cohorts are consistent with previously published reports after TKA [7,15,38,42]. In addition, given the relatively recent implementation of this technology and the desire to have a mean of 2 years followup, we were limited by the total number of surgical procedures performed using CCGs.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the impact of the extremely positive or negative outliers in function would have a greater impact with smaller cohorts, leading to increases in the SDs of the clinical outcome scores and perhaps masking true differences between the two groups. However, the SDs of the clinical outcomes scores seen in both cohorts are consistent with previously published reports after TKA [7,15,38,42]. In addition, given the relatively recent implementation of this technology and the desire to have a mean of 2 years followup, we were limited by the total number of surgical procedures performed using CCGs.…”
Section: Discussionsupporting
confidence: 84%
“…Patients were seen or contacted for clinical followup at 2 weeks, 6 weeks, 6 months, 1 year, and 2 years postoperatively. UCLA [42], SF-12 [38], and Oxford knee scores [15] were compared between the two cohorts both preoperatively and at their most recent followup visit. Patients in the CCG cohort had increased UCLA, SF-12 physical component, and Oxford knee scores preoperatively (p = 0.001 to 0.03; Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…However, in addition to being lengthy, it requires a licensing fee to use, potentially limiting broad implementation. The 12‐item Oxford Knee and Hip Scores assess pain and function and were designed to measure outcomes following joint replacement surgery 17, 18. They are widely used in clinical studies and joint replacement registries, but how applicable they are to the general OA population is unclear, and they require a license for use.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical data were collected preoperatively and at one and five years following surgery by the same independent assessor and included Oxford Knee Score (OKS) [9,20], American Knee Society functional and objective scores (AKSS-fcn and AKSS-obj respectively) [17], and Tegner activity scale [25]. One year was determined as the principal follow-up interval because it has been demonstrated that the majority of the functional improvement after knee arthroplasty is within the first year [7,21,6,23]; a subset of these patients have attained five years' follow-up and we also present their five-year data.…”
Section: Methodsmentioning
confidence: 99%